THE ROLE OF SOCIAL PARTNERSHIP IN COMMUNITY LIFE - Abdukodir Otaboev (Web of Journals Publishing, 2023)
This article briefly describes the reforms carried out in the Republic of Uzbekistan on the role of social partnership in the life of society.
Keywords: state, society, social partnership, separation of powers, law, state power, political institutions, civil society.